Respuesta eléctrica de películas gruesas del sistema SnO2-TiO2, conformadas con polvos cerámicos obtenidos a través del método pechini - Montenegro, A.; Cerón, N.; Ponce, M.; Castro, M. S.; Varela, José Arana [UNESP]; Rodríguez, J. E. (Elsevier, 2007)
Tin oxide is the compound more used in the gas sensor production, mainly to reduce gases like CO and H2. Their electrical properties are strongly dependent of its surface. For this is of great importance to synthesize nanoscale tin oxide particles to use they later in the films conformation. The synthesis of SnO2-TiO2 nanoparticles by polymeric precursor method is reported in this work. The particles were characterized by DTA/TG, FT-IR, XRD and SEM. Also, the electrical response of thick films measured under oxygen and carbon monoxide atmospheres is was analyzed.
Electrical answer of the SnO2-TiO2 thick films shaping with ceramics powders obtained by Pechini method
Keywords: Electrical answer; Nanoparticles; Pechini; SnO2-TiO2